Breastfeeding in Pediatric Acute-Onset Neuropsychiatric Syndrome: An Italian Observational Study - Manuel Murciano; Davide Maria Biancone; Francesca De Luca; Denise Piras Marafon; Cristiana Alessia Guido; Cristiana Alessia Guido; Alberto Spalice (Frontiers Media S.A., 2021)
Objective: Pediatric acute-onset neuropsychiatric syndrome (PANS) is a condition defined by sudden onset of obsessive-compulsive symptoms and/or severe eating restrictions, along with at least two other cognitive, behavioral, or neurological symptoms. Its pathogenesis is unknown but it seems triggered by infections, metabolic disturbances, and other inflammatory reactions. PANS represents a neurodevelopmental problem and infant feeding can play a role. Breast milk is the ideal food for infants and influences children's brain, cognitive, and socio-emotional development.Methods: We enrolled 52 children diagnosed with PANS. We interviewed their parents in order to investigate perinatal history, infant feeding, neurologic development, and confounding factors like socio-economic status and region of origin. We subgrouped PANS patients into three subsets: those who only received human milk (HMO), those who only received infant formula, and those who received mixed feeding.Results: The cohort is composed of 78.9% males, with a median age of 11 years (range 7-17). We found some neurodevelopmental problems (13.5%): walking disorders, ASD, ADHD, oppositional attitude, and delayed psychomotor development. We found scholar performance deficits (25%), including language problems like dysgraphia, dyslexia, and dyscalculia. The achievement of some milestones in the development of the infant is affected in 73.1% of cases. Breastfeeding is not homogeneously practiced in Italy because of social, economic, and cultural phenomena. The richest and the poorest families (100%) in the sample choose breastfeeding, probably with a different approach and for different reasons (awareness or need). In the group of PANS patients fed with HMO, compared to the rest of the patients, we registered fewer cases of growth problems (0 vs. 12.9%; p = 0.14), school performance problems or the need for school support (19.1% vs. 29%; p = 0.42), and a delay in the age of babbling/speaking (range 4-20 vs. 7-36 months; p = 0.066).Conclusion: This is the first study that investigates the role of breastfeeding in the development of PANS. Promoting breastfeeding is important in the general population and also in PANS patients because it has an important social and global health impact, also during adult life. Further studies with a bigger population are needed to investigate the mechanisms underlying PANS and the role that breastfeeding may play in their short- and long-term neurodevelopment.